2019
DOI: 10.1002/biof.1514
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone biochanin A, a novel nuclear factor erythroid 2‐related factor 2 (Nrf2)‐antioxidant response element activator, protects against oxidative damage in HepG2 cells

Abstract: Isoflavones are one group of the major flavonoids and possess multiple biological activities due to their antioxidant properties. However, a clear antioxidant mechanism of dietary isoflavones is still remained to be answered. In this study, the effects of isoflavones on the nuclear factor E2‐related factor 2 (Nrf2)–antioxidant response element (ARE) signaling pathway and the underlying molecular mechanisms were investigated. Results showed that isoflavones are potential Nrf2–ARE activators while their activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 43 publications
(93 reference statements)
1
24
0
Order By: Relevance
“…The current study revealed that BA treatment significantly improved the number of Nrf2-positive cells in the alveolar bone. These results are consistent with a recent study by Liang et al (39), where BA was an effective Nfr2 activator. In addition, BA has the capability to counteract oxidative damages induced by LPS (33,40), high-fat diet (12) and D-galactosamine (41).…”
Section: Discussionsupporting
confidence: 94%
“…The current study revealed that BA treatment significantly improved the number of Nrf2-positive cells in the alveolar bone. These results are consistent with a recent study by Liang et al (39), where BA was an effective Nfr2 activator. In addition, BA has the capability to counteract oxidative damages induced by LPS (33,40), high-fat diet (12) and D-galactosamine (41).…”
Section: Discussionsupporting
confidence: 94%
“…10,11 Although soybean has been reported to produce Biochanin A, the concentration of this isoflavonoid is under the quantification limits, indicating that soybean can synthesize Biochanin A only in very low concentration. 12 Biochanin A has recently emerged as a multi-target and multi-functional compound to human cell, 13 with anti-inflammatory, 14 anticancer, 15 neuroprotective, 16 antioxidant, 17 hepatoprotective 18 and anti-COVID-19 19 properties. Despite these important advances, the role of Biochanin A in plant defence and its potential applications in plant disease management remain almost unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…BCA may occur as an aglycon and can also be used as a hormone alternative therapy. BCA plays complex roles in the regulation of multiple biological functions by binding DNA and some specific proteins or acting as a competitive substrate for some enzymes (Roberts et al, 2004; Křížová et al, 2019; Liang et al, 2019; Luo et al, 2019). BCA is the methylated precursor of the isoflavone genistein (GEN), which is another well-studied isoflavone.…”
Section: Introductionmentioning
confidence: 99%